Dissection of a grain yield QTL from wild emmer wheat reveals sub-intervals associated with culm length and kernel number - Deblieck, Mathieu; Szilagyi, Gergely; Andrii, Fatiukha; Saranga, Yehoshua; Lauterberg, Madita; Neumann, Kerstin; Krugman, Tamar; Perovic, Dragan; Pillen, Klaus; Ordon, Frank (Frontiers in Genetics, 2022)
Genetic diversity in wheat has been depleted due to domestication and modern breeding. Wild relatives are a valuable source for improving drought tolerance in domesticated wheat. A QTL region on chromosome 2Bs from wild emmer wheat (Triticum turgidum ssp. dicoccoides), conferring high grain yield under well-watered and water-limited conditions, was transferred to the elite durum wheat cultivar Uzan (T. turgidum ssp. durum) by the marker assisted backcross breeding approach. The 2B introgression line turned out to produce more yield, but also included negative traits that likely result from linkage drag. In this study, the respective 2BS QTL was subjected to fine-mapping, and a set of 17 homozygote recombinants were phenotyped at BC4F5 generation, under water-limited and well-watered conditions at the experimental farm in Israel, and at a high-throughput phenotyping platform (LemnaTec-129) in Germany. In general, both experimental setups allowed the identification of sub-QTL intervals related to culm length, kernel number, thousand kernel weight and harvest index. Sub-QTLs for kernel number and harvest index were detected specifically under either drought stress or well-watered conditions, while QTLs for culm length and thousand-kernel weight appeared under both conditions. Although no direct QTL for grain yield could be confirmed, plants with the sub-QTL for kernel number showed a higher grain yield than the recurrent durum cultivar Uzan under well-watered and mild drought stress conditions. We therefore suggest that this sub-QTL might be of interest for future breeding purposes.